2021
DOI: 10.3390/cells10082169
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes Protect Muscle Loss by miR-145-5p Activity Targeting Activin A Receptors

Abstract: Skeletal muscle mass is decreased under a wide range of pathologic conditions. In particular, chemotherapy is well known for inducing muscle loss and atrophy. Previous studies using tonsil-derived mesenchymal stem cells (T-MSCs) or a T-MSC-conditioned medium showed effective recovery of total body weight in the chemotherapy-preconditioned bone marrow transplantation mouse model. This study investigated whether extracellular vesicles of T-MSCs, such as exosomes, are a key player in the recovery of body weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The presence of miRNA-145 in EVs has been documented in small EVs in several diseases including cancer, such as ovarian cancer [ 104 ], where miRNA-145 has even been suggested as the most promising biomarker for the preoperative diagnosis of ovarian cancer [ 105 ]. miRNA-145 has also been reported in urinary EVs from prostate cancer patients [ 106 ], in vascular smooth muscle cells [ 107 ], colorectal cancer [ 108 ], hepatocarcinoma [ 109 ], cerebral injury [ 110 ], as well as its active role in the recovery of skeletal muscle mass in mice with chemotherapy [ 111 ], osteoarthritis [ 112 ], and pancreatic cancer [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of miRNA-145 in EVs has been documented in small EVs in several diseases including cancer, such as ovarian cancer [ 104 ], where miRNA-145 has even been suggested as the most promising biomarker for the preoperative diagnosis of ovarian cancer [ 105 ]. miRNA-145 has also been reported in urinary EVs from prostate cancer patients [ 106 ], in vascular smooth muscle cells [ 107 ], colorectal cancer [ 108 ], hepatocarcinoma [ 109 ], cerebral injury [ 110 ], as well as its active role in the recovery of skeletal muscle mass in mice with chemotherapy [ 111 ], osteoarthritis [ 112 ], and pancreatic cancer [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the reported EV‐associated miRNAs play promotive roles in the process of muscle wasting, a few studies focus on the inhibitive functions of those miRNAs. For instance, miR‐145‐5p present in EVs of tonsil‐derived mesenchymal stem cells (T‐MSCs) was found to be able to rescue muscle wasting both in vitro and in vivo 53 . MiR‐145‐5p can target two of the activin A receptors, ACVR2A and ACVR1B, therefore inhibiting the binding of activin A and its downstream processes, which regulate gene transcriptions of proteolytic enzymes 53 .…”
Section: The Biological Regulation Of Ev Cargoes In Skeletal Muscle W...mentioning
confidence: 99%
“…For instance, miR‐145‐5p present in EVs of tonsil‐derived mesenchymal stem cells (T‐MSCs) was found to be able to rescue muscle wasting both in vitro and in vivo 53 . MiR‐145‐5p can target two of the activin A receptors, ACVR2A and ACVR1B, therefore inhibiting the binding of activin A and its downstream processes, which regulate gene transcriptions of proteolytic enzymes 53 . And in this way, EV‐transferred miR‐145‐5p can inhibit muscle proteolysis and rescue skeletal muscle wasting induced by activin A 53 .…”
Section: The Biological Regulation Of Ev Cargoes In Skeletal Muscle W...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the authors showed that activin A induced Smad2/3 and FoxO1 nuclear translocation and transcriptional upregulation of Atrogin-1 and MuRF-1 genes, which resulted in muscle atrophy. Exosomal miR-145-5p released from tonsil-derived mesenchymal stem cells has been shown to maintain or improve skeletal muscle mass in various activin-A-elevated pathologic conditions ( Cho et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%